A dual perspective review on large language models and code verification - Dolcetti, Greta; Iotti, Eleonora (Frontiers in Computer Science, 2025)
Recent advances in Large Language Models (LLMs) have sparked significant interest in their application to code verification and the assessment of LLM-generated code safety. This review examines current research on the intersection of LLMs with software verification, focusing on two main aspects: the use of LLMs as verification tools and the verification of code produced by LLMs. We analyze the emerging approaches for integrating LLMs with traditional static analyzers and formal verification tools, including prompt engineering techniques and combinations with established verification frameworks. The review explores various verification methodologies, from standalone LLM applications to hybrid approaches incorporating traditional verification methods. We examine research addressing the safety assessment of LLM-generated code and investigate frameworks developed for vulnerability detection and repair. Through this analysis, we aim to provide insights into the current state of LLM applications in code verification, identify key challenges in the field, and outline important directions for future research in this rapidly evolving domain.